The compound effect of irradiation and familial pseudohyperkalemia on potassium leak from red blood cells. Issue 12 (26th October 2022) - Meli, Athinoula; Linger, Rachel; Stevens‐Hernandez, Christian J.; Gyongyver, Gyorffy; Marks, Denese C.; Aung, Htet Htet; Tan, Joanne C. G.; Cardigan, Rebecca; Bruce, Lesley J.; New, Helen V.
Abstract: Background: Familial pseudohyperkalemia (FP) is a rare asymptomatic condition characterized by an increased rate of potassium leak from red blood cells (RBC) on refrigeration. Gamma irradiation compromises RBC membrane integrity and accelerates potassium leakage. Here, we compared the effect of irradiation, applied early or late in storage, on FP versus non‐FP RBC. Study Design: Five FP and 10 non‐FP individuals from the National Institute for Health Research Cambridge BioResource, UK, and three FP and six non‐FP individuals identified by Australian Red Cross Lifeblood consented to the study. Blood was collected according to standard practice in each center, held overnight at 18–24°C, leucocyte‐depleted, and processed into red cell concentrates (RCC) in Saline Adenine Glucose Mannitol. On Day 1, RCC were split equally into six Red Cell Splits (RCS). Two RCS remained non‐irradiated, two were irradiated on Day 1 and two were irradiated on Day 14. RBCs were tested over cold storage for quality parameters. Results: As expected, non‐irradiated FP RCS had significantly higher supernatant potassium levels than controls throughout 28 days of storage ( p  < .001). When irradiated early, FP RCS released potassium at similar rates to control. When irradiated late, FP RCS supernatants had higher initial post‐irradiation potassium concentration than controls but were similar to controls by the end of storage (14 days post‐irradiation). No other parameters studied showed a significant difference between FP and control. Discussion: FP does not increase the rate of potassium leak from irradiated RBCs. Irradiation may cause a membrane defect similar to that in FP RBCs.